2016
DOI: 10.1016/j.celrep.2016.11.053
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Clock Neuron Network Features Diverse Coupling Modes and Requires Network-wide Coherence for Robust Circadian Rhythms

Abstract: Summary In animals, networks of clock neurons containing molecular clocks orchestrate daily rhythms in physiology and behavior. How various types of clock neurons communicate and coordinate with one another to produce coherent circadian rhythms is not well understood. Here, we investigate clock neuron coupling in the brain of Drosophila and demonstrate that the fly’s various groups of clock neurons display unique and complex coupling relationships to core pacemaker neurons. Furthermore, we find that coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 39 publications
6
58
2
Order By: Relevance
“…We classified flies as rhythmic only if they maintained activity rhythms for the entire 9-10 days. Finally, though the morning oscillator is thought to delay the evening peak of activity and thus control period length (22), the average period length of Pdf-specific per or tim-targeted flies (23.87 and 23.42 hours, respectively) was similar to controls (23.88 hours) ( Fig. 4C).…”
Section: Disruption Of Per or Tim In The Morning Oscillator (Pdf + S-mentioning
confidence: 89%
See 2 more Smart Citations
“…We classified flies as rhythmic only if they maintained activity rhythms for the entire 9-10 days. Finally, though the morning oscillator is thought to delay the evening peak of activity and thus control period length (22), the average period length of Pdf-specific per or tim-targeted flies (23.87 and 23.42 hours, respectively) was similar to controls (23.88 hours) ( Fig. 4C).…”
Section: Disruption Of Per or Tim In The Morning Oscillator (Pdf + S-mentioning
confidence: 89%
“…To test the effect of disrupting per or tim in both the morning and evening oscillators, we expressed our UAS-sgRNA constructs in the s-LNvs (including the 5 th s-LNv) and 3 CRY + LNds, with weak or variable expression in l-LNvs, DN1s, and non-clock neurons, using the Mai179-Gal4 driver ( Fig. 3A) (21,22,39,50). We found that 100% of flies CRISPR-targeted for per and tim in Mai179 + cells (Mai179-Gal4>per CRISPR and Mai179-Gal4>tim CRISPR ) were arrhythmic, while 91% of control flies (Mai179-Gal4>acp CRISPR ) remained rhythmic ( Fig.…”
Section: Disruption Of Per or Tim In Both Morning And Evening Oscillamentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpressing DBT S in the LNvs advances morning anticipation with no effect on evening anticipation, while overexpressing SGG in the same neurons advances both morning and evening anticipation (Stoleru et al 2005;Yao et al 2016), reflecting their effect on speeds of the individual molecular oscillators. Conversely, overexpressing DBT L in the LNvs slows the LNv clocks, yet delays evening anticipation with no effect on morning anticipation (Fig.…”
Section: The Effects Of Different Kinases On the S-lnv And Lnd Clocksmentioning
confidence: 99%
“…The loss of the dorsal termini in Unc-5 expressing LNvs was not accompanied by 181 changes in the proportion of flies displaying endogenous circadian rhythms in locomotor activity, nor did 182 it produce a shortening of its free-running period (Figures 3A-C, S4B, and Table 1). The expression of the 183 mutant clock kinase Dbt LONG only in the PDF expressing LNvs coherently sets the period of free-running 184 sleep/activity rhythms to approximately 27 hours through a PDF-mediated resetting of the molecular 185 clocks of target clock neurons (Yao and Shafer, 2014)(Yao et al, 2016). Remarkably, the co-expression 186 of Unc-5 with Dbt LONG in the LNvs did not prevent these neurons from lengthening the free-running 187 period of locomotor rhythms or delaying the evening peak of activity on the first day of free-run ((Figure 1883A, C, D, S4B andTable 1).…”
mentioning
confidence: 99%